Locating Economic Risks for Adolescent Mental and Behavioral Health: Poverty and Affluence in Families, Neighborhoods, and Schools. Issue 2 (28th February 2017) - Coley, Rebekah Levine; Sims, Jacqueline; Dearing, Eric; Spielvogel, Bryn
Abstract : Research has identified risks of both poverty and affluence for adolescents. This study sought to clarify associations between income and youth mental and behavioral health by delineating economic risks derived from family, neighborhood, and school contexts within a nationally representative sample of high school students ( N  =   13, 179, average age 16). Attending schools with more affluent schoolmates was associated with heightened likelihoods of intoxication, drug use, and property crime, but youth at poorer schools reported greater depressive and anxiety symptoms, engagement in violence, and for male adolescents, more frequent violence and intoxication. Neighborhood and family income were far less predictive. Results suggest that adolescent health risks derive from both ends of the economic spectrum, and may be largely driven by school contexts.